Acacia mangium plantations in PT Musi Hutan Persada, South Sumatera, Indonesia - Siregar, S.T.H.; Hardiyanto, E.B.; Gales, K. (Center for International Forestry Research, 1999)
PT Musi Hutan Persada, a forestry company growing wood for pulp in South Sumatra manages about 200 000 ha of forest plantations, 90% of which consists of Acacia mangium. Most of the plantations are in an area with high rainfall and on red-yellow podzolic soil with inherently poor fertility and low pH. Inter-rotation site productivity and management have been identified by the company as one of the crucial issues for sustaining the long-term productivity of its plantations. This paper describes the study plan for inter-rotation site productivity and management of A. mangium plantations in PT Musi Hutan Persada. The experiment tests the on-site effect of different treatments of organic matter or aboveground biomass management. Information from earlier work indicates that most A. mangium biomass and three major nutrients (N, P and K) is in the wood, and harvesting will remove around 200 kg N, 45 kg P and 240 kg K per hectare. Litter production of an 8-year old stand was about 13 t ha –1 and about 70% of its mass will be lost in one year.